Surviving the triple threat: Left main and triple vessel coronary disease treated with coronary artery bypass grafting: A case report - Shrivastav, Aditya; Sahu, Priyansh Kumar; Tiwaskar, Suhas; Luharia, Anurag; Somankar, Saurabh; Das, Sarthak; Thitame, Sunil (Indian Journal of Case Reports, 2025)
Left main coronary artery – Triple vessel disease is a critical cardiovascular condition requiring urgent intervention. Early diagnosis and timely revascularization play a vital role in determining patient outcomes. We present a 58-year-old male with a history of myocardial infarction who was discharged but returned with worsening dyspnea and chest pain. Coronary angiography revealed severe stenosis of the left main, left anterior descending, and left circumflex arteries, along with total occlusion of the right coronary artery. The patient underwent coronary artery bypass grafting and was later found to have left ventricular dysfunction with an ejection fraction of 44% on follow-up echocardiography. Heart failure therapy was optimized according to the clinical situation. Exclusion of alternative causes through laboratory and radiological investigations supported the diagnosis. A structured strategy involving hemodynamic stabilization, early mobilization, and cardiac rehabilitation was implemented. At 1-year follow-up, although the ejection fraction remained low, the patient showed improved functional capacity. This case highlights the importance of early identification, coordinated multidisciplinary care, and rehabilitation in managing complex coronary artery disease. It also underlines the disconnect between anatomical severity and biomarker levels, emphasizing the need for further investigation into similar clinical paradoxes and their therapeutic implications.